Evaluation of the Effectiveness of Surgical Treatment of Chronic Purulent Otitis Media with Simultaneous Tympanoplasty - Z., Narbaev; K. K., Kosimov (American Journal of Bioscience and Clinical Integrity, 2025)
In this scientific article, the balance organs of humans and vertebrates are the vestibular apparatus. In addition to the vestibular apparatus, the skin, musculoskeletal and visual sensory reflex play a significant role in maintaining balance in a person. The complex relationships formed in the process of these reflections ensure balance.